Cover Picture: Heterogeneous One‐Pot Carbonylation and Mizoroki–Heck Reaction in a Parallel Manner Following the Cleavage of Cinnamaldehyde Derivatives (Chem. Eur. J. 34/2017). Issue 34 (11th April 2017) - Hattori, Tomohiro; Ueda, Shun; Takakura, Ryoya; Sawama, Yoshinari; Monguchi, Yasunari; Sajiki, Hironao
Abstract : Carbon monoxide and styrene derivatives, which can both be generated by a palladium on carbon‐catalyzed carbon–carbon bond cleavage reaction of cinnamaldehyde derivatives, were thoroughly employed for the simultaneously proceeding Mizoroki–Heck and carbonylation reactions. More information can be found in the Full Paper by Y. Monguchi, H. Sajiki et al. onpage 8196 .